2023
DOI: 10.1021/acs.orglett.3c00487
|View full text |Cite
|
Sign up to set email alerts
|

Acylsilane Directed Rh-Catalyzed Arene C–H Alkylation with Maleimides and Visible-Light-Induced Siloxycarbene-Amide Cyclization: [3 + 2] Carbo-Annulation in Ru Catalysis

Abstract: We herein demonstrate the acylsilane-directed Rh-catalyzed arene C−H bond alkylation with maleimides. The resulting derivatives were utilized in visible-light-induced intramolecular siloxycarbene-amide cyclization for the synthesis of new tricyclic γ-lactams. In parallel, we also harnessed the same acylsilane and maleimide units through [3 + 2] carbo-annulation by using Ru-catalysis. A wide range of maleimides and aroylsilanes were used to establish the broadness of these transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Furthermore, photochemical irradiation of olefin-tethered acylsilanes affords stable cyclopropane adducts, and photochemical irradiation of ester-tethered acylsilanes produces a mixture of structural isomers following 1,2-carbonyl addition of the visible light-induced siloxy carbene to the ester. The discovery that nucleophilic siloxy carbene intermediates can undergo 1,2-carbonyl addition to proximal esters presents further opportunities to exploit siloxy carbene reactivity . Moreover, the 1,2-alkoxy migration that occurred to generate the minor structural isomer described in Figure represents an intriguing transformation that warrants further investigation.…”
Section: Acylsilanes In Transition-metal-catalyzed Alkylation/annulat...mentioning
confidence: 99%
“…Furthermore, photochemical irradiation of olefin-tethered acylsilanes affords stable cyclopropane adducts, and photochemical irradiation of ester-tethered acylsilanes produces a mixture of structural isomers following 1,2-carbonyl addition of the visible light-induced siloxy carbene to the ester. The discovery that nucleophilic siloxy carbene intermediates can undergo 1,2-carbonyl addition to proximal esters presents further opportunities to exploit siloxy carbene reactivity . Moreover, the 1,2-alkoxy migration that occurred to generate the minor structural isomer described in Figure represents an intriguing transformation that warrants further investigation.…”
Section: Acylsilanes In Transition-metal-catalyzed Alkylation/annulat...mentioning
confidence: 99%
“…2-Phenyl-3a,8a-dihydroindeno [1,2-c]pyrrole-1,3,8(2H)-trione (7aa). 15 GP-3 was carried out with 2-iodobenzaldehyde 2a (58 mg, 0.25 mmol), N-phenylmaleimide 6a (53 mg, 0.30 mmol), Pd(OAc) 2 (5.6 mg, 10 mol %, 0.025 mmol), AgOAc (83 mg, 0.50 mmol), NaOAc ( [1,3]dioxole-5-carbaldehyde 2f (69 mg, 0.24 mmol), N-ethylmaleimide 6r (38 mg, 0.30 mmol), Pd(OAc) 2 (5.6 mg, 10 mol %, 0.025 mmol), AgOAc (83 mg, 0.50 mmol), NaOAc (21 mg, 0.25 mmol), and TFA (2 mL) at 100 °C for 6 h in an oil bath. Purification of the crude material by silica gel column chromatography (petroleum ether:ethyl acetate = 70:30 to 65:25) furnished the product 7fr (43 mg, 63%) as a colorless solid.…”
Section: Preparation Of (E)-3-(2-iodophenyl)-1-phenylprop-2-en-1-one ...mentioning
confidence: 99%
“…13,14 Recently, the research group of Das revealed a strategy for succinimide-fused indane derivatives via Ru-catalyzed [3 + 2] cyclization of acyl silane motifs with maleimides (Scheme 1a(ii)). 15 The research groups of Chatani and Jeganmohan explored a Pd-catalyzed [3 + 2] annulation of maleimides with benzamides and benzoic acids via benzylic C(sp 3 )−H and meta-C(sp 2 )−H bond activation by bis-chelating amino acid ligands in 2021, 2022, and 2023 (Scheme1b). 16,17 Kumar et al unveiled the synthesis of succinimide-fused unsymmetrical 9,10-dihydrophenanthrenes via the Heck strategy using aryl iodides and maleimides in 2020.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations